Deadly catch Lake Victoria's AIDS crisis - Integrated Regional Information Networks ([Nairobi : United Nations Office for the Coordination of Humanita rian Affairs, Integrated Regional Information Networks, 2005)
A short documentary on Lake Victoria's AIDS crisis.
Co-produced by Hugo Raimi and David Gough ; camera & editing, David Gough.
Narrator: Mumbi Kaigwa.
In English and Luo with some English subtitles.
Keywords: AIDS (Disease) -- Kenya; Documentary films